2018
DOI: 10.1186/s13075-018-1515-1
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CCP-positive patients with RA have a higher 10-year probability of fracture evaluated by FRAX®: a registry study of RA with osteoporosis/fracture

Abstract: BackgroundPositive anticyclic citrullinated peptide (anti-CCP+) is associated with bone loss in patients with rheumatoid arthritis (RA). However, whether overall positivity or specific levels of anti-CCP are associated with prevalent fracture or a 10-year probability of fracture remains unclear.MethodsThis interim analysis of an RA registry was conducted at Chang Gung Memorial Hospital in Kaohsiung (CGMHK) for RA-related osteoporosis/fracture. Consecutive patients with RA who had visited the rheumatology clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 34 publications
1
28
1
1
Order By: Relevance
“…Prevalence of osteoporosis in RA patients varied greatly among studies. The previously reported prevalence of osteoporosis in RA patients was 22.0% [23], 25.0% [24], 30.0% [25,26], 32.4% [27], 40.4% [28] while in one study it was as high as 79.8% [29]. In patients with recent-onset RA (< 6 months duration), osteoporosis was found in 25.0% of the patients [30].…”
Section: Discussionmentioning
confidence: 93%
“…Prevalence of osteoporosis in RA patients varied greatly among studies. The previously reported prevalence of osteoporosis in RA patients was 22.0% [23], 25.0% [24], 30.0% [25,26], 32.4% [27], 40.4% [28] while in one study it was as high as 79.8% [29]. In patients with recent-onset RA (< 6 months duration), osteoporosis was found in 25.0% of the patients [30].…”
Section: Discussionmentioning
confidence: 93%
“…Positive anti-CCP status is primarily associated with bone loss, disability, disease duration and disease activity in RA patients 17 . Our cross study showed this relationship between clinical characteristics, disease activity, joints damages and Anti-CCP status in Algerian RA patient from western Algeria (Sidi Bel Abbes region in particular ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ACPAs are associated with RA severity. RA patients with ACPAs exhibit more severe radiographic damage than those without ACPAs (7)(8)(9)(10). Many studies have suggested that ACPAs play a pathophysiologic role in RA (11).…”
Section: Introductionmentioning
confidence: 99%